2019
DOI: 10.15446/dyna.v86n209.70897
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil pH sampled by two methodologies used in precision agriculture in farms under crop rotation

Abstract: This study aimed to characterize the spatial variability of pH in soils of two farms in the state of Paraná, Brazil, based on two different sampling methods used in precision agriculture, by means of geostatistical analyzes. The first method of sampling the pH grid consisted in the collection of soil samples by the traditional method (1 point / ha). The second method of pH determination was by on-the-go soil sensor (200 points / ha). The spherical model was better suited to most semivariograms, regardless of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies have revealed that the higher nugget values (0 to 1) are, the smoother and more accurate the layers, but some nugget values in this study were outside the limit; hence, the RMSE was used (Clark, 2010). Additionally, research has reported that RMSE values close to 1 suggest higher accuracy (Benoit et al, 2019; Ferraz et al, 2019; Setianto & Triandini, 2015). From Table 6, it can be seen that RMSE values range from 0.513 to 1.303, indicating acceptable levels of accuracy on the individuals, suggesting that these layers are recommendable for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that the higher nugget values (0 to 1) are, the smoother and more accurate the layers, but some nugget values in this study were outside the limit; hence, the RMSE was used (Clark, 2010). Additionally, research has reported that RMSE values close to 1 suggest higher accuracy (Benoit et al, 2019; Ferraz et al, 2019; Setianto & Triandini, 2015). From Table 6, it can be seen that RMSE values range from 0.513 to 1.303, indicating acceptable levels of accuracy on the individuals, suggesting that these layers are recommendable for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, some crops may need to be tolerant to specific soil properties such as pH, which are not always favourable for diverse cropping. For instance, ideal soil conditions for growing rice include relatively low pH levels that ensure optimal soil submergence while being sufficient to keep salt, harmful ion and reduction product levels low (Ferraz et al, 2019).…”
Section: Ph Variationmentioning
confidence: 99%
“…In order to refine management practices and evaluate agricultural effects, it is crucial to understand the spatial variability of soil properties, which is a relevant factor in a production system aimed at sustainability through site-specific management (Ferraz et al, 2019). Moreover, spatial characteristics allow us to quantify several natural phenomena (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2010) stated that the knowledge of spatial distribution associated with the definition of management zones through regionalized maps could result in a more efficient application of agricultural fertilizers, a reduction of input costs, an optimized use of fertilizers as well as economic and environmental gains. Management zones could also be defined by soil electrical conductivity sensors (Mallarino and Wittry, 2004), which are already available to farmers (Ferraz et al, 2019). According to Mulla (2013), the use of high technology, such as soil sensors to optimize the use of fertilizer, appears a viable alternative to promote the mitigation of increasing environmental pollution .…”
Section: Introductionmentioning
confidence: 99%